The glacial geomorphology of the ice cap Piedmont Lobe landsystem of East Myrdalsjokull, Iceland - D.J.A. Evans; Marek Ewertowski; Chris Orton; David Graham (2018)
A surficial geology and geomorphology map of the forelands of the Sandfellsjökull and Oldufellsjökull piedmont lobes of the east Mýrdalsjökull ice cap is used to characterise the historical and modern landscape imprint in a glacial landsystems context. This serves as a modern analogue for palaeoglaciological reconstructions of ice cap systems that operated outlet lobes of contrasting dynamics, but the subtle variability in process-form regimes is encoded in the geomorphology. The landsystems of the two piedmont lobes reflect significantly different process-form regimes, and hence contrasting historical glacier dynamics, despite the fact that they are nourished by the same ice cap. The Sandfellsjökull landsystem displays the diagnostic criteria for active temperate glacier operation, including arcuate assemblages of inset minor push moraines and associated flutings, kame terrace and ice-dammed lake deposits, linear sandar directed by overridden moraine arcs, and since 1945, features, such as ice-cored, pitted, and glacially pushed outwash fans that are linked to englacial esker networks representative of recession into an overdeepening. Moraine plan forms have also changed from weakly crenulated and discontinuous curvilinear ridges to sawtooth features and crevasse-squeeze ridges and till eskers in response to changing proglacial drainage conditions. The Oldufellsjökull landsystem displays subtle signatures of jökulhlaup-driven surges, including sparse and widely spaced moraine clusters that are separated by exceptionally long flutings. The subtlety of the surge imprint at Oldufellsjökull was recognised only by comparison with nearby Sandfellsjökull, suggesting that palaeo-surging has likely been under-estimated in the ancient landform record. Hence, the simple imprint of sparse and widely spaced moraine clusters that are separated by exceptionally long flutings should be included as possible surge-diagnostic criteria.